KENDALA PEMBANGUNAN PROVINSI DAERAH KEPULAUAN: STUDI KASUS PROVINSI KEPULAUAN RIAU - Ari Mulianta Ginting (Jurnal Politica, 2013)
This Study discusses current situation in the Riau Archipelagic Province, which needs a special development approach. Its analysis is made based on library studies and reports of discussions of Bill on Development Acceleration of the Archipelagic Provinces. This research looks further into the constraints facing in Riau. Its finding reveals some problems, for instance, geographical conditions, low general allocation fund, and poor education and health services. Therefore, central government’s intervention is needed, together with DPR, to issue special policy to accelerate development in the archipelagic province.